Slavery and Bondage in Asia, 1550-1850 Towards a Global History of Coerced Labour - Ekama, Kate; Hellman, Lisa; van Rossum, Matthias (Dependency and Slavery Studies, 2022)
This book offers an Asia-centred story of bondage and coerced labour. Spanning the western Indian Ocean to Japan, and the 16th to the 19th century, it follows coercion from the regulation of sales to post-abolition labour contracts. In doing so, it highlights long lines, similarities, contrasts and interregional contacts of this history, and places Asia firmly within the discussion of slavery and coercion on a global scale.